How might blockchain technology be used in the food supply chain? A systematic literature review - Retno Astuti; Luki Hidayati (Cogent Business & Management, 2023)
The complexity of the food supply chain necessitates the implementation of traceability systems. The traceability system optimized the food supply chain management. Blockchain technology promises a new distributed ledger, which provides various uses by solving several traceability issues. Unfortunately, the present study does not completely address the use, opportunities, and challenges of blockchain technology in the food supply chain. Therefore, this study investigates the general knowledge regarding blockchain technology (the concept, features, and type of blockchain) and its use in the food supply chain. The findings of this study assist in gaining a better understanding and information regarding how to strengthen the traceability system in the food supply chain by optimizing the use of blockchain technology. The findings confirmed that the use of blockchain technology in the food supply chain was primarily for traceability, with public/private blockchain assisting as a popular platform. The transaction data is about the product origin information, transaction information, and product label information. The use of blockchain in the food supply chain has the benefit of enhancing food supply chain traceability and transparency. The challenges are the need for significant financial, human resources, and infrastructure investment, limited technical knowledge of stakeholders, significant product changes, the rapid development of the global supply chain, the potential for data manipulation, and policy change.
Keywords: 650; blockchain; food supply chain; Information & Technology Management; Operation Management; technology adoption; traceability; transparency